The Many Benefits of Urban Green Spaces - Abu Kasim, Junainah; Mohd Yusof, Mohd Johari; Mohd Shafri, Helmi Zulhaidi (CSID Journal of Infrastructure Development, 2019)
Recently, the ideology of greenery city has received global attention which aimed to address the issues of rapid urbanization, population growth and climate change. Urban green spaces (UGS) seem as the most essential asset that could help cities to mitigate the adverse effects of rapid urbanization and urban sprawl in a sustainable way. It plays a vital role in our cities as an urban lung, discharging oxygen to reduce the city’s heat, the wall for harmful air pollution and offer greatest benefits in term of environment, social and economy to a city. However, the presence of UGS as one of the important sectors in urban planning are always been neglected. Nevertheless, UGS are loved by everyone however when it turns to the need, then it is often apparent as a liability and claim as non-commodity goods in a planning development process. Hence, this paper aims to understand the many benefits of urban green space development in the contemporary of urban sustainability thought. The systematic review has been carried out through scientific online database, documentation and relevant related papers.